Prognostic Nomograms Combined Adjuvant Lenvatinib for Hepatitis B Virus–related Hepatocellular Carcinoma With Microvascular Invasion After Radical Resection - Bai, Shilei; Hu, Lei; Liu, Jianwei; Sun, Minmin; Sun, Yanfu; Xue, Feng (Frontiers in Oncology, 2022)
Background: Microvascular invasion (MVI) has been established as one of the most important contributors to the prognosis of primary hepatocellular carcinoma (HCC). The objective of this study was to investigate the potential effect of postoperative adjuvant therapy with Lenvatinib on the long-term prognosis after radical resection in hepatitis B virus (HBV)-related HCC patients with MVI, as well as to predict the long-term survival based on nomograms. Methods: Data from 293 HBV-related hepatocellular carcinoma patients with histologically confirmed MVI who underwent R0 resection at Eastern Hepatobiliary Surgery Hospital (EHBH) was retrospectively analyzed. Fifty-seven (57) patients received postoperative adjuvant therapy with Lenvatinib, while 236 patients did not. The survival outcome of patients who received postoperative adjuvant Lenvatinib versus those who did not was analyzed. Results: The 1-year, 2-year recurrence rates and survival rates of the Lenvatinib group were improved compared to the non-Lenvatinib group (15.9%, 43.2% vs 40.1%, 57.2%, P=0.002; 85.8%, 71.2% vs 69.6%, 53.3%, P=0.009, respectively). Similar findings were also observed after Propensity Score Matching (PSM) compared to non-PSM analyses. The 1-year, 2-year recurrence rates and survival rates were more favorable for the Lenvatinib group compared to the non-Lenvatinib group (15.9%, 43.2% vs 42.1%, 57.4%, P=0.028; 85.8%, 71.2% vs 70.0%, 53.4%, P=0.024, respectively). As shown by univariate and multivariate analyses, absence of adjuvant Lenvatinib treatment was identified as an independent risk factor for recurrence and survival. The established nomograms displayed good performance for the prediction of recurrence and survival, with a C-index of 0.658 and 0.682 respectively. Conclusions: Postoperative adjuvant therapy with Lenvatinib was associated with improved long-term prognosis after R0 Resection in HBV-related HCC patients with MVI, which could be accurately predicted from nomograms.